Administrative Capacity in Consular Services: A Literature Review on Institutional Readiness in Serving Indonesian Migrant Workers - Agussalim Agussalim; Amirul Mustofa; Sarwani Sarwani; Dian Ferriswara (Dynamics Social : International Journal of Social Sciences and Communication, 2026)
Consular services have become a critical site of state intervention in the governance of international labor migration, particularly for migrant-sending countries such as Indonesia whose citizens depend on overseas missions for administrative protection and access to public services abroad. Despite the growing importance of consular institutions in safeguarding migrant workers’ rights and welfare, existing scholarship remains fragmented, offering limited conceptual integration of how administrative capacity shapes institutional readiness in cross-border public service delivery. Addressing this gap, this article presents a structured narrative–integrative literature review that synthesizes international peer-reviewed studies on administrative capacity, policy capacity, consular services, and migrant worker protection published in the last five years. Drawing on Administrative Capacity Theory as the core framework, complemented by Public Service Theory, Policy Implementation Theory, Street-Level Bureaucracy, and Institutional Theory, the review systematically analyzes how different dimensions of capacity configure institutional readiness in consular services. The findings reveal that institutional readiness emerges from the interaction of four interrelated dimensions: human resource capacity, organizational and procedural capacity, institutional and coordination capacity, and resource and infrastructure capacity. Rather than functioning as isolated determinants, these dimensions collectively shape how consular institutions translate formal mandates into service outcomes under conditions of transnational governance, legal pluralism, and fluctuating demand. The review further demonstrates that frontline discretion, coordination gaps, procedural rigidity, and uneven resource allocation are recurrent patterns across the literature, underscoring the dynamic and practice-based nature of administrative capacity in consular contexts. Theoretically, this article contributes to public administration scholarship by extending administrative capacity frameworks into the underexplored domain of cross-border public services and by integrating previously segmented theoretical perspectives into a coherent conceptual synthesis. By reframing consular services as institutionally embedded public service systems rather than solely diplomatic functions, the article advances understanding of institutional readiness in migrant worker protection and provides a robust analytical foundation for future empirical and comparative research in international public administration.